Academic Fraud during the Covid-19 Pandemic for High School Students - Alhamuddin Alhamuddin; Dinar Nur Inten; Rabiatul Adwiyah; Andi Murniati; Ahmad Fanani (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
This study aims to determine the academic fraud students committed to doing assignments during the Covid-19 pandemic. This study used a descriptive method with a quantitative approach. Data collection was done by randomly distributing Google Forms to high school students in West Java Province. There were about 540 samples that were successfully captured in this study. The data analysis technique was carried out employing descriptive statistics. The results showed that as many as 88.3% of students stated that they committed academic fraud in doing the assignments given to them by the teacher. The fraud was done by copying and pasting a friend's assignment from the internet and doing things without obligation. It was done because there was no particular action from the teacher against cheating students. Particular policies need to be made by schools; namely, the teacher instills the values of Honesty and other anti-corruption values in the learning process. Besides that, the use of technology is to determine whether there is an element of plagiarism in student assignments. Parents at home also need to instill anti-corruption values ​​in their children from an early age so that they are familiar with these things.